The Contribution of Self-Regulated Learning to the Academic Procrastination Behavior of Fast Track Students of the Master of Sports Education FIK UNNES - AnggieAP, Bambang Priyono, Ranu Baskora, Anggie Ade Pratiwi (Journal of Physical Education and Sports, 2024)
This research aims to determine the contribution of self-regulated learning to the academic procrastination of fast track students at the Master of Sports Education, Faculty of Sports Science, UNNES. There is an influence of self-regulated learning on the academic procrastination of fast track students who are working on theses and theses so that the proposed hypothesis can be accepted, students who have high levels of self-regulated learning will have a high level of academic procrastination.This research uses a mixed method type of research. Mixed methods research design (mixed methods research design) is a procedure for collecting, analyzing and "mixing" quantitative and qualitative methods in a study or series of studies to understand the problems in the research. This research uses a grounded theory method approach. This research is specifically for FIK UNNES sports education fast track students who are working on theses and dissertations. The variables in this research were measured using two measuring instruments, namely Self-regulated Learning and academic procrastination, which focused on a Likert scale model that had been modified using four alternative answer choices. The research results were then processed using the Pearson product moment correlation coefficient, so that validity was obtained.Based on the results of data analysis, it can be shown that there is a positive and significant correlation between the Self-regulated learning variables proposed in this research and it is accepted, there is an influence of Self-regulated learning on academic procrastination, namely (β / regression coefficient) = -0.816, which means that every additional 1% of the self-regulated learning value, then the participation value increases -0.816. The regression coefficient is negative, so it can be said that the direction of influence of variable X on Y is negative following the direction. Meanwhile, the value of the coefficient of determination or (R Squre) is 43%, meaning that the influence of Self-regulated Learning on Academic Projrastinasi only contributes 43%, the remainder is influenced by other variables.